3D heterostructured pure and N-Doped Ni3S2/VS2 nanosheets for high efficient overall water splitting. (10th April 2018) - Zhong, Xiongwei; Tang, Jun; Wang, Jingwei; Shao, Mengmeng; Chai, Jianwei; Wang, Shuangpeng; Yang, Ming; Yang, Ye; Wang, Ning; Wang, Shijie; Xu, Baomin; Pan, Hui
Abstract: Exploring earth-abundant electrocatalysts with high activity and low-cost for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is vital to energy harvesting and storage, such as fuel cell and effective overall water splitting. Herein, novel heterostructures (Ni3 S2 /VS2 ) without nitrogen (N) and with N doping are reported as superior electrocatalysts for the OER and HER, respectively. The heterostructure without doping shows enhanced OER performance with an extremely low overpotential (227 mV at 10 mA/cm 2 ) due to increased active sites and fantastic interfaces as well as unique structure. Moreover, N-doped Ni3 S2 /VS2 (N-Ni3 S2 /VS2 ) shows high electrocatalytic HER performance with a low HER overpotential (151 mV at 10 mA/cm 2 ), because the N-doping greatly improves conductivity and increases large amounts of catalytic active sites. Finally, we construct a two-electrode electrolyzer system (Ni3 S2 /VS2 //N-Ni3 S2 /VS2 ) and it achieves a current density of 10 mA/cm 2 at a low cell voltage of 1.648 V. Our findings demonstrate that structure design and doping can effectively improve the catalytic activities of nanomaterials for OER and HER. Graphical abstract: Highlights: We propose a novel heterostructure Ni3 S2 /VS2 with abundant active sites and interfaces. The Ni3 S2 /VS2 exhibits a low OER overpotential of 227 mV at 10 mA/cm 2 . The N-Ni3 S2 /VS2 demonstrates a low HER overpotential of 151 mV at 10 mA/cm 2 . A two-electrode system shows good performance on overall water-splitting with an overpotential of 1.648 V at 10 mA/cm 2 .